The role of algal organic matter in the separation of algae and cyanobacteria using the novel “Posi” - Dissolved air flotation process - Rao Hanumanth Rao, Narasinga; Yap, Russell; Whittaker, Michael; Stuetz, Richard M.; Jefferson, Bruce; Peirson, William L.; Granville, Anthony M.; Henderson, Rita K. (Elsevier, 2017)
Algae and cyanobacteria frequently require separation from liquid media in both water treatment and algae culturing for biotechnology applications. The effectiveness of cell separation using a novel dissolved air flotation process that incorporates positively charged bubbles (PosiDAF) has recently been of interest but has been shown to be dependent on the algae or cyanobacteria species tested. Previously, it was hypothesised that algal organic matter (AOM) could be impacting the separation efficiency. Hence, this study investigates the influence of AOM on cell separation using PosiDAF, in which bubbles are modified using a commercially available cationic polyelectrolyte poly(N, N-diallyl-N,N-dimethylammonium chloride) (PDADMAC). The separation of Chlorella vulgaris CS-42/7, Mychonastes homosphaera CS-556/01 and two strains of Microcystis aeruginosa (CS-564/01 and CS-555/1), all of which have similar cell morphology but different AOM character, was investigated. By testing the cell separation in the presence and absence of AOM, it was determined that AOM enhanced cell separation for all the strains but to different extents depending on the quantity and composition of carbohydrates and proteins in the AOM. By extracting AOM from the strain for which optimal separation was observed and adding it to the others, cell separation improved from <55% to >90%. This was attributed to elevated levels of acidic carbohydrates as well as glycoprotein-carbohydrate conjugations, which in turn were related to the nature and quantity of proteins and carbohydrates present in the AOM. Therefore, it was concluded that process optimisation requires an in-depth understanding of the AOM and its components. If culturing algae for biotechnology applications, this indicates that strain selection is not only important with respect to high value product content, but also for cell separation.
Keywords: Algae harvesting; Cyanobacteria; Dissolved air flotation; Polymer coated bubbles